Hubungan Antara Penggunaan Google Classroom Pada Pembelajaran Daring Terhadap Hasil Belajar Matematika Siswa Kelas IV-B SDN Kembangan Utara 012 Petang - Sintyia Purnamasari; Khaola Rachma Adzima (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2022)
This study aims to see the relationship between the use of Google Classroom on learning outcomes in mathematics at SDN Kembangan Utara 012 Petang. This research is a quantitative research using survey method. The population in this study were students of class IV-B SDN Kembangan Utara 012 Evening, totaling 30 students. The data collection technique used in this research is in the form of a questionnaire by distributing it through Google Form. This questionnaire was conducted to identify the relationship between Google Classroom and mathematics learning outcomes. The results of the research calculations with the partial test obtained tcount = 3.649 > ttable 2.042 with a significance of 0.000 <0.05, the result is that H1 is accepted and H0 is rejected, which means that there is a significant relationship between the use of Google Classroom on the mathematics learning outcomes of grade IV-B students at SDN Kembangan Utara 012 evening with a coefficient of determination of 67.8% while the remaining 32.2% is connected by other variables outside the study.